Urgensi Laporan Tahunan pada Perseroan Terbatas Pasca Permenkum Nomor 49 Tahun 2025: Sosialisasi bagi Anggota IAI Wilayah Banten - Arrizal, Nizam Zakka; Indradi, Donny; Sari, Siska Diana; Taufiq, Abd Rohman; Prastiwi, Vivi Nanda (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
The annual report is an instrument of accountability and legal compliance that the Board of Directors of a Limited Liability Company (PT) is obliged to submit to the General Meeting of Shareholders (GMS), as mandated by Article 66 and Article 78 paragraph (2) of Law Number 40 of 2007 on Limited Liability Companies. The enactment of Regulation of the Minister of Law Number 49 of 2025 introduces new technical provisions on the approval, registration, and uploading of annual reports through the Legal Entity Administration System (SABH). However, understanding among business actors, accounting practitioners, and company management regarding this obligation remains limited, creating a risk of administrative sanctions, ranging from written warnings to the blocking of access to General Legal Administration (AHU) services. This community service activity aims to enhance participants' understanding of the legal basis, procedures, content, audit obligations, and legal consequences of a PT's annual report. It was carried out as a webinar organized by the Indonesian Institute of Accountants (IAI) Banten Chapter on Wednesday, 24 June 2026, using interactive lectures, regulatory exposition, case studies, and a question-and-answer session. The results show improved participant understanding of Article 66 and 78 paragraph (2) of the PT Law, the mechanism for submitting annual reports through a notary and SABH, criteria triggering mandatory audit by a public accountant, shareholders' rights at the annual GMS, and legal consequences including release and discharge and administrative sanctions. This activity is expected to encourage better corporate compliance and strengthen synergy between the legal and accounting professions in realizing good corporate governance.